The effects of 22°C and 4°C storage of platelets on vascular endothelial integrity and function. (March 2016) - Baimukanova, Gyulnar; Miyazawa, Byron; Potter, Daniel R.; Gibb, Stuart L.; Keating, Sheila; Danesh, Ali; Beyer, Ashley; Dayter, Yelena; Bruhn, Roberta; Muench, Marcus O.; Cap, Andrew P.; Norris, Philip J.; et al.
Abstract : BACKGROUND: Although a majority of the studies conducted to date on platelet (PLT) storage have been focused on PLT hemostatic function, the effects of 4°C PLTs on regulation of endothelial barrier permeability are still not known. In this study, we compared the effects of room temperature (22°C) stored and (4°C) stored PLTs on the regulation of vascular endothelial cell (EC) permeability in vitro and in vivo. STUDY DESIGN AND METHODS: Day 1, Day 5, and Day 7 leukoreduced apheresis PLTs stored at 4 or 22°C were studied in vitro and in vivo. In vitro, PLT effects on EC permeability and barrier function, adhesion, and impedance aggregometry were investigated. In vivo, using a mouse model of vascular leak, attenuation of vascular leak and circulating PLT numbers were measured. RESULTS: Treatment of EC monolayers with Day 5 or Day 7 PLTs, stored at both 22°C and 4°C, resulted in similar decreases in EC permeability on average. However, analysis of individual samples revealed significant variation that was donor dependent. Additional in vitro measurements revealed a decrease in inflammatory mediators, nonspecific PLT‐endothelial aggregation and attenuated loss of aggregation over time to TRAP, ASPI, ADP, and collagen with 4°C storage. In mice, while 22°C and 4°C PLTs both demonstrated significant protection against vascular endothelial growth factor A (VEGF‐A)‐induced vascular leak 22°C PLTs exhibited increased protection compared to 4°C PLTs. Systemic circulating levels of 4°C PLTs were decreased compared to 22°C PLTs. CONCLUSIONS: In vitro, 4°C‐stored PLTs exhibit a greater capacity to inhibit EC permeability than 22°C‐stored PLTs. In vivo, 22°C PLTs provide superior control of vascular leak induced by VEGF‐A. This discrepancy may be due to increased clearance of 4°C PLTs from the systemic circulation.